Glyphosate and aminomethylphosphonic acid chronic risk assessment for soil biota. (14th July 2016) - von Mérey, Georg; Manson, Philip S.; Mehrsheikh, Akbar; Sutton, Peter; Levine, Steven L.
Abstract: Glyphosate is a broad‐spectrum herbicide used widely in agriculture, horticulture, private gardens, and public infrastructure, where it is applied to areas such as roadsides, railway tracks, and parks to control the growth of weeds. The exposure risk from glyphosate and the primary soil metabolite aminomethylphosphonic acid (AMPA) on representative species of earthworms, springtails, and predatory soil mites and the effects on nitrogen‐transformation processes by soil microorganisms were assessed under laboratory conditions based on internationally recognized guidelines. For earthworms, the reproductive no‐observed‐effect concentration (NOEC) was 472.8 mg glyphosate acid equivalent (a.e.)/kg dry soil, which was the highest concentration tested, and 198.1 mg/kg dry soil for AMPA. For predatory mites, the reproductive NOEC was 472.8 mg a.e./kg dry soil for glyphosate and 320 mg/kg dry soil for AMPA, the highest concentrations tested. For springtails, the reproductive NOEC was 472.8 mg a.e./kg dry soil for glyphosate and 315 mg/kg dry soil for AMPA, the highest concentrations tested. Soil nitrogen‐transformation processes were unaffected by glyphosate and AMPA at 33.1 mg a.e./kg soil and 160 mg/kg soil, respectively. Comparison of these endpoints with worst‐case soil concentrations expected for glyphosate (6.62 mg a.e./kg dry soil) and AMPA (6.18 mg/kg dry soil) for annual applications at the highest annual rate of 4.32 kg a.e./ha indicate very low likelihood of adverse effects on soil biota. Environ Toxicol Chem 2016;35:2742–2752. © 2016 The Authors. Environmental Toxicology and Chemistry Published by Wiley Periodicals, Inc. on behalf of SETAC.